Original paperMultisector dosimetry in the immediate post-implant period: significant under dosage of the prostate base - Kirschner, Austin N.; Sathiaseelan, Vythialingam; Zhang, Yunkai; David, James; Kalapurakal, John A. (Journal of Contemporary Brachytherapy, 2014)
Purpose : While there are several reports of prostate multisector dosimetry data obtained from CT or MRI scans performed at intervals ranging from 14-70 days after prostate brachytherapy (PB), there are no reports on multisector dosimetry performed in the immediate post-implant period. This study was undertaken to determine the results of prostate multisector dosimetry performed in the immediate post-implant period on day 1 post-implant dosimetry after 125 I PB. Material and methods: The day 1 post-implant CT-based V100 and D 90 were determined for the prostate base (PGB) and compared to doses to the entire gland (PG), mid-gland (PMG), and apex (PA) in 75 patients who underwent 125 I PB to a dose of 144 Gy. Similar multisector dosimetry was also performed on the pre-implant ultrasound volume study scans of these patients. Results: All patients had good quality implants. On day 1 post-implant multisector dosimetry there was significant under dosage of the PGB for both V100 and D 90 . The average magnitude of under dosage of PGB compared to PMG and PA was 17.2% and 22.7% for V100 and 44.6 Gy and 31.7 Gy for D 90 , respectively. On pre-implant multisector dosimetry there was no statistically significant under dosage of the PGB for V100, but the PGB D 90 was significantly lower compared to PMG and PA, however, the average magnitude of under dosage was small at 12.6 Gy and 4.2 Gy, respectively. Conclusions : This report demonstrates that similar to other reports on more delayed post-implant multisector dosimetry data, there is significant under dosage of the prostate base in the immediate post-implant period based on day 1 post-implant dosimetry. The clinical significance of this under dosage remains to be defined and further studies are warranted.